الأخطاء اللغوية الشائعة في استعمال العربية في المجتمع البروناوي - Yahya Duraib (UIN Fatmawati Sukarno Bengkulu, 2018)
AbstractThe importance of Arabic is reflected in the fact that it is the key to Islamic and Arab culture. It allows the learner to know how civilized and intellectual a nation has been raised on the throne of the world for centuries. It has left a great cultural heritage in various arts and various sciences. . The most important reasons that led to the prevalence of this disturbing number of errors in the language of Hadad, the language of the last messages of God - the Almighty - the status of the Seal of the prophets and messengers to tell her slaves of God, and the most important treatments.Key word: Common linguistic errors; The use of Arabic in the community of Brunei.